FEAST AND FAITH: AN ETHNOGRAPHIC STUDY OF COMMUNICATION AND CULTURE IN NOEMUTI'S FOLE MAKO - Mokos, Inosensius Enryco (Paradigma: Jurnal Kajian Budaya, 2026)
This article investigates Fole Mako, a significant traditional communal feast in Noemuti, North Central Timor, Indonesia. The event is analyzed in the context of its deliberate timing to coincide with the 100th anniversary of the Sacred Heart of Jesus Parish and the consecration of a new church. Using the Ethnography of Communication framework, a detailed analysis is provided of the intricate communication practices, profound cultural meanings, and vital social functions embedded within this elaborate feast. Data for the study were meticulously collected through direct observation and engaged participation. The findings reveal that Fole Mako is much more than a mere banquet. It serves as a profound mechanism for strengthening shared communal identity, expressing collective gratitude, and demonstrating an extraordinary capacity to harmonize traditional customs with contemporary religious celebrations. This enduring cultural practice highlights the community’s agency in fostering social cohesion and cultural resilience, proving that traditions can thrive in an evolving social context.